2010
DOI: 10.1088/0957-4484/21/16/165705
|View full text |Cite
|
Sign up to set email alerts
|

Tin-oxide-coated single-walled carbon nanotube bundles supporting platinum electrocatalysts for direct ethanol fuel cells

Abstract: Novel tin-oxide (SnO(2))-coated single-walled carbon nanotube (SWNT) bundles supporting platinum (Pt) electrocatalysts for ethanol oxidation were developed for direct ethanol fuel cells. SnO(2)-coated SWNT (SnO(2)-SWNT) bundles were synthesized by a simple chemical-solution route. SnO(2)-SWNT bundles supporting Pt (Pt/SnO(2)-SWNTs) electrocatalysts and SWNT-supported Pt (Pt/SWNT) electrocatalysts were prepared by an ethylene glycol reduction method. The catalysts were physically characterized using TGA, XRD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…9, the forward peak current density (390 A g À1 ) on the Pt/PEDOT/ER-GO is 5 times greater than that of bare Pt/GC electrode. According to the previous reports [44,45], the forward peak current densities on Pt/C and Pt/CNTs are 300 A g À1 and 350 A g À1 , respectively.…”
Section: 5mentioning
confidence: 62%
“…9, the forward peak current density (390 A g À1 ) on the Pt/PEDOT/ER-GO is 5 times greater than that of bare Pt/GC electrode. According to the previous reports [44,45], the forward peak current densities on Pt/C and Pt/CNTs are 300 A g À1 and 350 A g À1 , respectively.…”
Section: 5mentioning
confidence: 62%
“…Due to the sulfonation of PVA, the intensity of the diffraction pattern for PVA is decreased [48]. Moreover, the XRD peaks obtained at 2θ = 38.65, 45.36, and 68.11 correspond to the presence of Pt particles [49,50]. The presence of small peaks of 2θ values of Pt suggests that these particles were deeply embedded on the surface of the developed IPMC membrane.…”
Section: Sem and Edxmentioning
confidence: 99%
“…It has been reported that SnO 2 exactly acts as the modifier for the enhancement of the electrochemical surface area (ECSA), and an appropriate amount of SnO 2 can reliably promote EOR performance. [21,38,39] For the PdCuSn 20 sample, the surface Sn and SnO 2 composition is 1.5 and 62.5 %, respectively, suggesting that a great amount of SnO 2 on the surface may block the active site of the catalysts, hence retarding the EOR activity of the catalysts. In terms of PdCuSn 10 and PdCuSn 15 , an appropriate amount of SnO 2 on the surface may slightly enhance the I f /I b ratio.…”
Section: Effect Of Reduction Temperatures On the Structural And Electmentioning
confidence: 99%